Studi Pengembangan Jaringan Distribusi Air Bersih Di Kecamatan Muara Kelingi Kabupaten Musi Rawas - Anna Emiliawati; Nurlaila Nurlaila; Ilham Kurniawan (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
This research was conducted as one of the efforts to realize the physical development of drinking water infrastructure and facilities that are oriented to the principle of integration and harmony between the needs and the potential of available resources. The aim is to provide an alternative network system for th development of clean water distribution networks in Muara Kelingi District due to the limitations of surface water. The scope of the study is limited to the collection of secondary data in the form of meteorological data, population data, topographic data and land use. In addition, the primary data collected is sondir data used to design a science production unit. Analysis of the availability of reliable water discharge using the F.J Mock Method and calculating domestic and non-domestic clean water requirements based on population projections in the next 25 years. Pipeline network simulation is calculated and examined with the watercad program. The clean water supply system is distributed by gravity from surface water sources, namely the Kelingi River with an IPA production capacity of 30 liters/s with a reservoir capacity of 500 m3. The investment costs incurred for the development of this network amounted to Rp 35,534,658,000.00. Financial analysis using NPV and BCR methods is carried out on a simulated network system. From the analysis carried out, it obtained a decent water distribution network system from a technical and financial perspective.